Fundamentals of mechatronics - Jouaneh, Musa (Australia : Cengage Learning Asia Pte Ltd, 2013)
Fundamentals of mechatronics is designed to serve as textbook for an undergraduate course in mechatronics system design.
Chapter 1. Introduction to mechatronics -- Chapter 2. Analog circuits and components -- Chapter 3. Semiconductor electronic devices and digital circuits -- Chapter 4. Microcontrollers -- Chapter 5. Data acquisition and microcontroller/PC interfacing -- Chapter 6. Control software -- Chapter 7. Sensors -- Chapter 8. Actuators -- Chapter 9. Feedback control -- Chapter 10. Mechatronics projects.
Includes index.
Keywords: MECHATRONICS